Recognition and Strengthening the Customary Land Ownership in Central Borneo Province - Nur Putri Hidayah; Sholahuddin Al-Fatih (Jurnal Hukum Novelty, 2019)
Introduction to The Problem: The rapid flow of globalization has brought indigenous peoples to prolonged horizontal and vertical conflicts. The majority of conflicts triggered by who has the right to own the land and functionalize it. The land that belongs to indigenous peoples and it inherited from generation to generation, suddenly taken by investors and it even supported by the government. The indigenous people are often victimized and forced out from their customary lands. They who try to claim the rights sometimes experience obstacles because of the stronger and dominant government position in the court. One of these conflicts occurred in the Dayak community in Central Borneo Province.Purpose/Objective Study: This study aims to determine the problems experienced by indigenous peoples in Central Borneo Province, as well as to find out the mechanism for establishing a legal protection system in order to provide recognition and strengthening ownership of customary land in the Central Borneo Province.Design/Methodology/Approach: This study uses normative research methods, with statute approaches and conceptual approaches.Findings: there are serious problems experienced by indigenous people in Central Borneo Province, related to customary land in their territory. However, there are legal safeguards that can be carried out through formal and administrative land recognition.